Adaptación y evaluación de las propiedades psicométricas de la BAS-3 para población adolescente de Tucumán (Argentina) (2013)
This article describes the adaptation and evaluation of psychometric properties of the BAS-3 Adolescent Socialization Battery in adolescents from Tucumán (Argentina). A total of 381 adolescents, between the ages of 10 and 15 that attend state and public schools, were evaluated with the BAS-3. The participants were administered the test with their parents’ consent. A two-factor solution explaining the 53.13 % of the variance was found. The statistical relations observed account for the presence of primary, secondary and third factors of socialization. The study provides data of Argentinean adolescents in relation to the psychometric properties of the test indicating its sensibility to the evaluation of social behavior self-perception.Keywords: socialization, self-perception, socialization battery, adolescents, psychometric properties.